Menegoisasikan Identitas Seksual dan Identitas Religius: Pengalaman Perempuan Kristen Berorientasi Homoseksual: - Marina Berlian Sarah Djami; Muhammad Syafiq (Psyche 165 Journal, 2021)
Becoming a lesbian as well as a follower of a religion that opposes homosexuality creates an ambivalent and contradictory experience. This study aims to reveal the personal experiences of four homosexually oriented Christian women in Surabaya. All participants are members of Protestant Christian church congregations with different denominations. Data were collected using semi-structured interviews and analyzed using an interpretive phenomenological analysis technique. The results of this study reveal three main themes, namely: living in two worlds, reconciling homosexual identity with religion, and making life decisions. The first theme reflects the dilemma experienced by the subjects when they realized that their choice as a homosexual was a sin in the perspective of their religion but they could not be able to force themselves to be a heterosexual woman. The second theme describes how the subjects tried to compromise between their homosexual orientation and their religious teachings. The last theme contains how choices are made when homosexual identity cannot be compromised with religious identity. This study concludes that most of the participants are trying to become a devout Christian and at the same time be able to engage in the same-sex sexual orientation. Keywords: homosexual identity, religious identity, lesbian, Christian Abstrak Menjadi lesbian sekaligus menjadi pemeluk suatu agama yang menentang homoseksualitas melahirkan pengalaman yang ambivalen dan kontradiktif. Penelitian ini bertujuan untuk mengungkap pengalaman personal empat perempuan Kristen yang berorientasi homoseksual di Surabaya. Seluruh partisipan merupakan bagian dari anggota jemaat gereja Kristen Protestan dengan denominasi yang berbeda. Data dikumpulkan menggunakan wawancara semiterstruktur dan dianalisis dengan teknik analisis fenomenologi interpretatif. Penelitian ini berhasil mengungkap tiga tema utama yaitu: hidup dalam dua dunia, mendamaikan diri, dan mengambil keputusan hidup. Tema pertama mencerminkan dilema yang dialami para subjek ketika menyadari pilihannya sebagai homoseksual adalah dosa namun tidak mampu memaksakan diri untuk menyukai lawan jenis. Tema kedua menggambarkan bagaimana para subjek berupaya mengkompromikan antara orientasi homoseksualitasnya dengan ajaran agamanya. Tema terakhir memuat bagaimana pilihan diambil ketika identitas homoseksual tidak dapat dikompromikan dengan identitas religius. Hasil penelitian ini menyimpulkan bahwa sebagian besar partisipan berupaya menjadi seorang Kristen yang taat dan sekaligus dapat menjalani orientasi seksual sesama jenis.